Analyses of mRNA Profiling through RNA Sequencing on a SAMP8 Mouse Model in Response to Ginsenoside Rg1 and Rb1 Treatment - Zhang, Shuai; Zhu, Dina; Li, Hong; Zhang, Haijing; Feng, Chengqiang; Zhang, Wensheng (Frontiers in Pharmacology, 2017)
ABSTRACT Ginsenoside Rg1 and Rb1 are the major ingredients in two medicines called QiShengLi (Z20027165) and QiShengJing (Z20027164) approved by China. These ingredients are believed to mitigate forgetfulness. Numerous studies have confirmed that GRg1 and GRb1 offer protection against Alzheimer’s disease (AD), and our morris water maze experiment also indicated that GRg1 and GRb1 may attenuate memory deficits in the seven-month-old SAMP8 mice; however, comprehensive understanding of their roles in AD remains limited. This study systematically explored the mechanism at the genome level of the anti-AD effects of GRg1 and GRb1 in a senescence-accelerated mouse prone 8 (SAMP8) model through deep RNA sequencing. A total of 74,885 mRNA transcripts were obtained. Expression analysis showed that 1,780 mRNA transcripts were differentially expressed in SAMP8 mice compared with the SAMP8+GRg1 mice. Moreover, 1,066 significantly dysregulated mRNA transcripts were identified between SAMP8 and SAMP8+GRb1 mice. Analyses according to gene ontology and the Kyoto Encyclopedia of Genes and Genomes revealed that oral administration of GRg1 and GRb1 improved the learning performance of the SAMP8 mouse model from various aspects, such as nervous system development and mitogen-activated protein kinase signaling pathway. The most probable AD-related transcriptional responses after medication were predicted and discussed in detail. This study is the first to provide a systematic dissection of mRNA profiling in SAMP8 mouse brain in response to GRg1 and GRb1 treatment. We explained their efficacy thoroughly from the source (gene-level explanation). The findings serve as a theoretical basis for the exploration of GRg1 and GRb1 as functional drugs with anti-AD activity.